Multimetric analysis uncovers time-dependent climate forcings from China’s 2.3-fold cropland reactive nitrogen emissions - Peng Xu; Zhenzhong Zeng; Huizhong Shen; Min Hu; Mingxu Liu; Cheng Gong; Yilin Chen; Chaopu Ti; Geng Li; Xuejing Wang; Yi Zheng; Si-Liang Li; et al. (Proceedings of the National Academy of Sciences, 2026)
China is the largest emitter of cropland gaseous reactive nitrogen (Ngr, including NH 3 , N 2 O, and NOx), which greatly affects regional air quality, climate change, and human health. Despite the substantial spatial and temporal variations in cropland Ngr emissions, their driving mechanisms and net climate change forcings (either cooling or warming) remain unclear. Using revised emission estimates and bottom–up mass flow-based approaches, we evaluated the spatiotemporal changes in and key drivers of China’s cropland Ngr emissions from 1978 to 2023. We assessed the relative contribution of China’s cropland Ngr emissions to climate change via multiple metrics (global warming and temperature potentials). China’s cropland Ngr emissions increased by approximately 2.3-fold from 1978 to 2023. The pace of this increase decelerated over time, from 0.17 Tg N·y −2 before 1996 to 0.15 Tg N·y −2 during 1997–2005 and −0.05 Tg N·y −2 after 2005. Population growth and N-intensive animal-sourced food production accounted for 31.7% and 23.2% of this historical emission change, respectively. The net climate change forcing of Ngr varies with scale. Currently, China’s cropland Ngr emissions in 2017 at the county level impart a net cooling effect ascribed to short-lived NH 3 and NOx emissions, but this forcing shifts in sign and magnitude to a warming effect over a one-hundred-year time horizon, primarily through long-lived N 2 O emissions. Our findings suggest that a combination of metrics can comprehensively and adequately capture short-, medium-, and long-term climate impacts and that achieving climate targets will conspire against Ngr mitigation efforts for environmental protection goals.